2020
DOI: 10.1002/ange.202001870
|View full text |Cite
|
Sign up to set email alerts
|

Ibotenic Acid Biosynthesis in the Fly Agaric Is Initiated by Glutamate Hydroxylation

Abstract: The fly agaric, Amanita muscaria, is widely known for its content of the psychoactive metabolites ibotenic acid and muscimol. However, their biosynthetic pathway and the respective enzymes are entirely unknown. 50 years ago, the biosynthesis was hypothesized to start with 3‐hydroxyglutamate. Here, we build on this hypothesis by the identification and recombinant production of a glutamate hydroxylase from A. muscaria. The hydroxylase gene is surrounded by six further biosynthetic genes, which we link to the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Their bioactivity is due to their structural similarity to the neurotransmitters glutamate and GABA and their binding to respective receptors in the brains of both invertebrates and vertebrates. The recent discovery of the biosynthetic gene cluster for the compounds revealed that their biosynthesis initiates from glutamate and makes it possible to identify additional Amanita species producing these compounds on a genetic basis ( Obermaier & Müller 2020 ). Another psychotropic alkaloid produced by Agaricomycete fruiting bodies is psilocybin produced by several Psilocybe species ( Fricke et al 2017 , Torrens-Spence et al 2018 ).…”
Section: Results: Developmentally Expressed Gene Classes In the ...mentioning
confidence: 99%
“…Their bioactivity is due to their structural similarity to the neurotransmitters glutamate and GABA and their binding to respective receptors in the brains of both invertebrates and vertebrates. The recent discovery of the biosynthetic gene cluster for the compounds revealed that their biosynthesis initiates from glutamate and makes it possible to identify additional Amanita species producing these compounds on a genetic basis ( Obermaier & Müller 2020 ). Another psychotropic alkaloid produced by Agaricomycete fruiting bodies is psilocybin produced by several Psilocybe species ( Fricke et al 2017 , Torrens-Spence et al 2018 ).…”
Section: Results: Developmentally Expressed Gene Classes In the ...mentioning
confidence: 99%
“… During the biosynthesis, the Fe­(II)/α-ketoglutarate (αKG)-dependent oxygenase TqaL catalyzes the oxidative cyclization of 1 to form the aziridine-ring containing 2 , which is converted into AIB followed by aziridine-ring opening and subsequent oxidative decarboxylation (Figure S1A). TqaL is a rare enzyme, as most of the reported Fe­(II)/αKG-dependent oxygenases that accept free amino acids, such as IDO, GriE, AsnO, VioC, and IboH, catalyze common hydroxylation reactions. Two unusual Fe­(II)/αKG-dependent oxygenases, HrmJ and BelL, which generate the cyclopropane rings with opposite stereoconfigurations in hormaomycins and belactosins, respectively, were recently reported. , Therefore, TqaL is the only known enzyme in this superfamily that has been biochemically characterized for aziridine formation.…”
Section: Introductionmentioning
confidence: 99%